Findings of some biochemical and haematological in cows with hypophosphatemia and effect of phosphorous in treatment - Mahmut Ok; Hasan Güzelbekteş; İsmail Şen; Alparslan Coşkun; Aliye Sağkan Öztürk; Şebnem Canikli (Eurasian Journal of Veterinary Sciences)
The purpose of this study was to determine change of some biochemical and haematological parameters in cows with hypophosphatemia, and to detect effect of phosphorous in treatment of disease. 19 cows with hypophosphatemia were used as material in this study. Phosphorus treatment was performed to animals. The serum phosphorus concentrations in the cows were very low (2.61 mg/dl), after phosphorus treatment, while serum phosphorus level in the cows was reached to normal range (5.74 mg/dl) limit. The TP (P<0.05), ALT (P<0.005), Fe (P<0.05), RBC (P<0.005), PCV (P<0.005) and Hb (P<0.05) levels did show difference before and after treatment, but this values were within normal range limits. In conclusion, blood phosphorus level under 1.5 mg/dl could be develop of postparturient haemoglobinuria and anemia in the cows, blood phosphorus level under 2.5 mg/dl might be observed symptoms of anorexia, decraese of milk production and light weakness in the cows. Effective of phosphorous apply in treatment of disease was determined.